HbS-Sicilian (δβ)0-Thalassemia: A Rare Variant of Sickle Cell - Grace Onimoe; Genine Smarzo (Case Reports in Hematology)
Sickle cell disease (SCD) is caused by a mutation in the sixth codon of the β-globin gene on chromosome 11, which leads to a single amino acid substitution (glutamine to valine). Sickle-(δβ)0-thalassemia is a rare variant of sickle cell disease (delta-beta thalassemia occurring in association with sickle hemoglobin, HbS), sparsely reported in literature, and has been associated with symptomatology necessitating careful monitoring and follow-up. We describe a patient who presented with a newborn screen reported as “FS” and a negative family history for sickle cell disease and sickle cell trait. Subsequent gene sequencing studies demonstrated the presence of Sickle-(δβ)0-thalassemia. Clinical course has remained relatively stable for this patient now at 18 months of age without any SCD related symptomatology or complications. As this is a rare variant of SCD with potential complications, it is important to establish diagnosis towards planning comprehensive care.